Sistem Informasi Perdagangan Berbasis Web sebagai Media Promosi bagi Pedagang di Lapak Alun-Alun Tambolaka - Marselina Dada Kaka; Ardiyanto Dapadeda; Yunita Katarina Riti (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The development of information technology provides significant opportunities for businesses to utilize digital media as a means of promoting and managing culinary products. Alun-Alun Tambolaka Stalls is a center for community culinary activities with high economic potential, but still faces obstacles in terms of product promotion, information dissemination, and limited marketing reach. This research aims to design and build a web-based trade information system that can be used as a promotional medium for vendors at Alun-Alun Tambolaka Stalls. This system is designed to display complete product information, including product name, category, description, price, and product image, so that it can be easily accessed by the general public via the internet. The system development method used is the Waterfall method, which includes requirements analysis, system design, implementation, testing, and maintenance. This system has several key features, including a shop information page, product catalog, product categories, a login page, an admin dashboard, and merchant and product data management. The results of this study indicate that the web-based trade information system developed can help merchants promote their products more effectively and efficiently, expand their marketing reach, and facilitate the public's access to product information available at the Tambolaka Square stalls. Therefore, this system is expected to increase the competitiveness of local merchants and support the economic development of the local community.